A study on comparison of hematological, autonomic and respiratory parameters in male drinkers and non-drinkers of Karukutty village, Kerala - Kumar, SS; Angel, J; Elsa, M; Usha, R; Mukkadan, JK (Community Based Medical Journal, 2013)
The present study was undertaken to compare hematological, autonomic and respiratory parameters in male drinkers and non- drinkers to create awareness and to popularize the knowledge of good/bad effects of drinking. Two hundred and twenty two males with mean age 32±4 were involved in this study comprising of 110 chronic drinkers and 112 non-drinkers, who served as controls. Bleeding time was estimated by Duke Method clotting time was estimated by capillary tube method. Measurement of blood pressure was performed by using sphygmomanometry. Pulse Oximeter was used to measure saturation of hemoglobin (SPo2) and pulse rate. The analysis of data was done by SPSS 20.0. Mean bleeding time was higher in drinkers than non-drinkers. In contrast Clotting time was lower in drinkers. Systolic and diastolic pressure was almost equal in drinkers and non-drinkers. Pulse rate was slightly higher in drinkers than non-drinkers. SPo2 was equal in both drinkers and non-drinkers. We conclude that alcohol prolongs bleeding time and shortens clotting time, however this is contradictory. Alcohol enhances pulse rate may be by decreasing vagal activity and increasing sympathetic activity. Though alcohol causes vasodilation, we havent observed any change in blood pressure.Inspite of the fact alcohol consumption effects Spo2, no change is observed in spo2 in our study. Hence this study merits continuing with higher sample size. DOI: http://dx.doi.org/10.3329/cbmj.v2i2.16701 Community Based Medical Journal 2013 July: Vol.02 No 02: 62-66